Hydrogen sorption capacity of as-grown multiwalled nanotubes (MWNTs) - M. Sanip, Suhaila; Ismail, Ahmad Fauzi; Buang, Nor Aziah; A. Majid, Zaiton; Saidin, Mohd. Abdul Razis (2005)
In this work, Multiwalled Carbon Nanotubes (MWNTs) have been synthesized as hydrogen storage material for use in a proton exchange membrane fuel cell system. The carbon source used is a cheap feedstock (acetylene) mixed with an inert gas, nitrogen. The production of MWNTs was carried out in a furnace chamber at atmospheric pressure and has relatively low energy requirements. The gas feedstock, acetylene, was passed over the catalysts at temperatures between 600-800Â°C and carbon nanotubes were collected as black powder on the catalysts. The MWNTs produced were then characterized for their purity through FE-SEM and TEM. The as-grown MWNTs were found to be 90 % high in purity. The MWNTs produced have 11 concentric walls with diameters between 4 and 11.6 nm with the distance between layers being 0.345 nm corresponding to the lattice layers of graphite. As a result, better hydrogen adsorption characteristic was observed between the graphitic layers of the MWNTs. Due to the high purity of the as-grown MWNTs, no complex purification process will be required. The as grown MWNTs showed high volume of adsorption at 77K and room temperatures and this indicated that hydrogen gas was sufficiently adsorbed in the MWNTs via physisorption.